Development of integrated spermatophyta module potential of local plants on students' independence and concept mastery - Rifai Kasman; S Suhartini (Biosfer: Jurnal Pendidikan Biologi, 2022)
Biology learning emphasizes the interaction of students with the object being studied so that the utilization of local potential needs to be done. This study aims to reveal the feasibility and effectiveness of the integrated Spermatophyta module of local plant potential in the Taliabu Island Regency, North Maluku Province. The achievement target is to increase independence and mastery of concepts. This research is development research with the ADDIE model (analysis, design, development, implementation, evaluation). The developed module is assessed by experts, and its effectiveness is tested on the dependent variable. The research population was students of SMA Negeri 4 Pulau Taliabu with a total sample of 28 students of class X. The results showed the Spermatophyta module based on the validation of learning experts 96.25 (very feasible), and media experts 68.98 (decent). The test results of the Spermatophyta module are known to have a significant effect on increasing student learning independence based on the independent sample t-test of .044 (<0.05). The N-gain value for the experimental class is 0.30 (High) and the control class is 0.07 (low). The Spermatophyta module has a significant effect on mastery of concepts known from the results of the independent samples t-test of 0.001 (<0.05). The N-gain value for the experimental class is 0.57 (Quite Effective) and the control class is 0.38 (Not Effective). The conclusion of this study, the Spermatophyta module developed is feasible based on expert validation and tends to be effective for increasing independence, and effective for increasing concept understanding. The Spermatophyta module requires further testing using a larger sample to ensure its suitability and effectiveness